Effects of a vocabulary acquisition and assessment system on students’ performance in a blended learning class for English subject - Jia, Jiyou; Chen, Yuhao; Ding, Zhuhui; Ruan, Meixian (Computers and education, 2012)
Vocabulary acquisition and assessment are regarded as the key basis for the instruction of English as a second language. However, it is time-consuming, fallible and repetitive for the school teachers and parents to assess the proficiency of the students’ vocabulary acquisition. We customized the open source course management system Moodle to build the individualized vocabulary review and assessment functions for English instruction. This web-based system was integrated into the regular English instruction of an experiment class of Grade three in a junior middle school, i.e. it was used in one school hour almost every week for an entire school term. Within this blended learning environment, the students’ performance of the experiment class in the ordinary and especially vocabulary examinations throughout the school term was improved gradually and was better than that of the control class, so that it achieved number one among sixteen classes in the same grade at the final term examination, compared with number eight before this experiment. The survey and interview with the students also demonstrated the system’s valuable functions for vocabulary acquisition and listening comprehension, and showed the students’ favor to such a kind of syllabus design with the intelligent course management system. The implication of this research is that the blended learning of English class with the individualized vocabulary acquisition and assessment system can improve the students’ performance in vocabulary acquisition and in ordinary test. This system can also be applied in other English classes. ► We build a vocabulary acquisition and assessment functions for English instruction. ► The web-based system was integrated into English instruction of an experiment class. ► With this blended learning system, the students’ performance improvement was greater. ► The improvement was verified by ordinary school tests, student survey and interview. ► The improvement in vocabulary test was more remarkable than in ordinary tests.